Evaluation of Peripheral Zone Prostate Cancer Aggressiveness Using the Ratio of Diffusion Tensor Imaging Measures. (26th September 2017) - Onay, Aslihan; Ertas, Gokhan; Vural, Metin; Acar, Omer; Saglican, Yesim; Coskun, Bilgen; Akpek, Sergin
Abstract : Purpose . To evaluate the aggressiveness of peripheral zone prostate cancer by correlating the Gleason score (GS) with the ratio of the diffusion tensor imaging (DTI) measures. Materials and Methods. Forty-two peripheral zone prostate tumors were imaged using DTI. Regions of interest focusing on the center of tumor foci and noncancerous tissue were used to extract statistical measures of mean diffusivity (MD) and fractional anisotroy (FA). Measure ratio was calculated by dividing tumor measure by noncancerous tissue measure. Results . Strong correlations are observable between GS and MD measures while weak correlations are present between GS and FA measures. Minimum tumor MD (M D m i n ) and the ratio of minimum MD (r M D m i n ) show the same highest correlation with GS (both ρ = - 0.73 ). Between GS ≤ 7 (3 + 4) and GS ≥ 7 (4 + 3), differences are significant for all MD measures but for some FA measures. MD measures perform better than FA measures in discriminating GS ≥ 7 (4 + 3). Conclusion . Ratios of MD measures can be used in evaluation of peripheral zone prostate cancer aggressiveness; however tumor MD measures alone perform similarly.